Pengenalan Program Dekranasda Kota Probolinggo Sebagai Mitra Pemerintah Kota Probolinggo Dalam Pengembangan Pengrajin Berdaya - Veronica Sri Astuti Nawangsih; Nurul Jannah Lailatul Fitria (VIVABIO: Jurnal Pengabdian Multidisiplin, 2022)
Economic development in Indonesia is concerned with the creative industry. The concept of UMKM/IKM in the creative industry is a suitable combination for Indonesia in the era of globalization. MSMEs/IKMs prioritize production with local materials or local potentials. The implementation of the creative industry by MSMEs/IKM needs support from the government. So that the government cooperates with Dekranasda partners who have tasks that are relevant to the creative industry. As in Probolinggo City, the Probolinggo City Government cooperates with the Probolinggo City Dekranasda partner. Various programs are implemented to support the creative industry, such as the latest program from the Dekranasda of Probolinggo City. The program is the Dekranasda Outlet and the Great UMIK Application in Supporting the Creative Industry. However, not much is known about the Probolinggo City Dekranasda and its programs. So that the service team carried out service activities for FISIP UPM students, especially those who were concerned with entrepreneurship. The goal is to introduce the Probolinggo City Dekranasda and its programs as well as provide insight and direction for students to get directly involved in the creative industry. This service activity is held in the form of empowerment with pre-test activities, lectures accompanied by discussions, post-tests, and distribution of post-activity e-books. This activity can achieve indicators of success as indicated by the comparison of the results of the pre-test and post-test. Partners who initially did not understand, did not know, and were not interested turned into understanding, more familiar, and interested.Keywords: Dekranasda; Partner Program; Craftsman; Empowered. ABSTRAKPembangunan perekonomian di Indonesia konsen dengan industri kreatif. Konsep UMKM/IKM pada industri kreatif menjadi perpaduan yang sesuai untuk Indonesia di era globalisasi. UMKM/IKM mengutamakan produksi dengan bahan lokal atau potensi khas daerah. Pelaksanaan industri kreatif oleh UMKM/IKM perlu dukungan dari pemerintah. Sehingga pemerintah menggandeng mitra Dekranasda yang memiliki tugas yang relevan dengan industri kreatif. Seperti di Kota Probolinggo, Pemerintah Kota Probolinggo bekerjasama dengan mitra Dekranasda Kota Probolinggo. Berbagai program dilaksanakan untuk mendukung industri kreatif seperti program terbaru Dekranasda Kota Probolinggo. Program tersebut adalah Gerai Dekranasda dan Aplikasi UMIK Hebat Dalam Mendukung Industri Kreatif. Akan tetapi masih belum banyak mengetahui Dekranasda Kota Probolinggo dan programnya. Sehingga tim pengabdian melakukan kegiatan pengabdian untuk mahasiswa FISIP UPM, khususnya yang konsen pada kewirausahaan. Tujuannya untuk mengenalkan Dekranasda Kota Probolinggo dan programnya serta memberikan wawasan dan araha untuk mahasiswa terjun langsung pada industri kreatif. Kegiatan pengabdian ini diselenggarakan dengan bentuk pemberdayaan dengan kegiatan pre-test, ceramah disertai diskusi, post test, dan pembagiaan e-book pasca kegiatan. Kegiatan ini dapat mencapai indikator keberhasilan yang ditunjukkan dengan perbandingan hasil pre-test dan post-test. Mitra yang awalnya tidak paham, tidak mengenal, dan tidak tertarik berubah menjadi paham, lebih mengenal, dan tertarik.Kata Kunci: Dekranasda; Program Mitra; Pengrajin; Berdaya.